Mathematical puzzle based PV array configuration for GMP enhancement under non-uniform irradiation - Kansal, Isha; Pachauri, Rupendra (EAI Endorsed Transactions on Energy Web, 2020)
The performance exploration of the proposed PV array configurations is analysed during the shadowing conditions. The performance evaluation of total-cross-tied (TCT) and symmetric matrix-total-cross-tied (SM-TCT) pattern based electrical connections are assessed according to distinguish shadow test cases. The PV system's non-linear conduct is noted in terms ofI-V and P-V curves. During partial shading conditions (PSCs), multiple power points (MPP) are observed such as local MPP and global MPP. Both TCT and SM-TCT configurations are compared in terms of parameters Global MPP, fill factor (FF) and performance enhancement (PE) under the three distinct shadow test cases as (i) lamp post (ii) three cornered shading or structure shadow (iii) single vertex shading respectively.
Keywords: partially shaded PV array system; power enhancement; power loss; fill-factor; global maximum power point